CFD Simulations of Natural Cross Ventilation in Building with Different Opening Positions and Louver Slat-Angles in Moderately-Dense Urban Area - Lip Kean Moey,; Hussein Abubakar Kassam,; Kah Yau Yap,; Yew Hin Fam,; Vin Cent Tai ,; Tze Fong Go,; Mohammad Hossein Yazdi, (International Journal of Integrated Engineering, 2025)
In this study, CFD simulations with ANSYS 2021 R2 were performed on a targeted building with natural cross ventilation in urban area. The arrangement of the nine buildings has the planar area ratio of 0.25, which is considered moderately dense. The targeted building was with respective windward and leeward opening in the Middle-Middle, Top-Top, Bottom-Bottom, Bottom-Top, and Top-Bottom. The openings were without louver (NL) and equipped with louvers of 0°, 15°, 30°, or 45° slat-angles. The Grid Convergence Index (GCI) analysis found that the basic grid-size of 7.98 million cells is suitable for the simulation. Subsequent Factor of 2 (FAC2) analysis shows that the Sk-ε modified coefficient with enhanced wall function is the most suitable turbulence model. The simulations show maximum dimensionless streamwise mean velocities (U/Uref) and dimensionless kinetic energies (k/Uref2) occurred at respective level of the windward opening; and that increasing the louver slat-angle caused maximum U/Uref and k/Uref2 decreased at increasing Y/H.  The Y/H against U/Uref and k/Uref2 for Top-Top and Top-bottom opening configuration were of high values for each louver slat-angle. Windward with Top opening achieved higher dimensionless volume flow rate (DFR); with Top-Top opening configuration showed highest DFR for NL followed by louver slat-angle of 0o to 45o. Bottom-Bottom opening configuration shown significantly lowest DFR. This study demonstrates the importance of considering the effects of opening positions and louver slat-angles in an urban area on the performance of the natural cross ventilation for buildings.